Intraday Share Price Volatility and Leveraged ETF Rebalancing - Shum, Pauline; Hejazi, Walid; Haryanto, Edgar; Rodier, Arthur (Review of Finance, 2016)
Regulators and market participants are concerned about leveraged exchange-traded funds (ETFs)’ role in driving up end-of-day volatility through hedging activities near the market’s close. Leveraged ETF providers counter that the funds are too small to make a meaningful impact on volatility. For the period surrounding the financial crisis, 2006–11, we show that end-of-day volatility was positively and statistically significantly correlated with the ratio of potential rebalancing trades to total trading volume. The impacts were not all economically significant, but largest during the most volatile days. Given the predictable pattern of leveraged ETF hedging demands, implications for predatory trading are explored.